Endoscopic Balloon Dilation Followed By Intralesional Steroid Injection for Anastomotic Strictures After Esophagectomy: A Randomized Controlled Trial. (October 2018) - Hanaoka, Noboru; Ishihara, Ryu; Motoori, Masaaki; Takeuchi, Yoji; Uedo, Noriya; Matsuura, Noriko; Hayashi, Yoshito; Yamada, Takuya; Yamashina, Takeshi; Higashino, Koji; Akasaka, Tomofumi; Yano, Masahiko; et al.
Abstract : OBJECTIVE: Endoscopic balloon dilation (EBD) is a standard treatment for anastomotic strictures after esophagectomy, and requires multiple dilations. We conducted a randomized controlled trial to assess the efficacy of adding a steroid injection to EBD to reduce restricture. METHODS: Patients were randomized to receive EBD combined with either triamcinolone or placebo injection. The primary endpoint was the number of dilations required to resolve the stricture. The secondary endpoints were restricture‐free survival and adverse events. Patients with a dysphagia symptom score of ≥2 after esophagectomy with an endoscopy‐confirmed anastomotic stricture were included. A total of 50 mg of triamcinolone acetonide (50 mg/5 mL) or an identical volume of normal saline solution as a placebo was injected per site using a 25‐gauge needle immediately after EBD. Both the patient and treating physician were blinded to the treatment given. RESULTS: During the 4‐year study period, 65 patients were randomized to either the steroid group ( n = 33) or placebo group ( n = 32). The median number of EBDs required to resolve strictures was 2.0 (interquartile range, 1.0‐2.5) in the steroid group and 4.0 (interquartile range, 2.0‐6.8) in the placebo group ( p < 0.001). After 6 months of follow‐up, 39% of patients who had received steroid injections remained recurrence free compared with 16% of those who had received saline injections ( p = 0.002). No adverse events occurred during follow‐up. CONCLUSIONS: Steroid injection shows promising results for the prevention of stricture recurrence in patients who underwent EBD for anastomotic strictures.